TikTok Affordances Among Foreign Domestic Workers in Kuwait: Between Connective Leisure, Ethical Empowerment, and Migrant Regulation - Breteau, Marion (CyberOrient, 2025)
Three million women are employed as domestic workers in the Arab Gulf States. Originating from Africa and South Asia, they find themselves in highly precarious working conditions. TikTok, the most popular application in the Gulf, now counts users from this job category. By displaying their conditions and addressing issues of cultural adaptation, foreign domestic workers foster a new form of identity through TikTok. By exploring how they engage in the digital sphere, particularly through this application, the author argues that their digital affordances transcend the notion of migratory labor as temporary and non‐integrative. By spending time online, domestic workers distract themselves, allowing them to be anchored in the country of work. They do so through “connective leisure,” a concept that the article provides a conceptual definition to assess forms of media affordances beyond traditional functions of communication. The way foreign domestic workers use TikTok also sheds light on existing limitations in migration, labor, and media laws. By focusing on the case of Kuwait, the author explores how these limitations transform social media into platforms for experimenting with the ethics of visibility, domesticity, and digital self‐performance.